Hazard Identification, Risk Assessment and Risk Control (HIRARC) of Safety and Health Hazards at Old High-Rise Residential Building Facilities: Case Study at Larkin Jaya Flat, Johor Bahru - Ramlee, Umar Suffian; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2023)
A high-rise residential building is a form of multi-unit house constructed on a single parcel of land. The rising cost of land in cities has made this type of housing more popular every year. In high-rise residences, there are a number of shared facilities. So, the work of maintaining the high-rise facilities must be well-organized and kept in the best shape as possible, especially in older high-rise residential. On the other hand, all buildings, whether they are historic or not, need to be taken care of regularly. Before moving on to the following stage, which is maintenance, it is necessary to undertake a risk assessment in order to identify the risks. HIRARC approach is used in this research to achieve the first objective which is identify the risk of the old high-rise residential facilities to safety and health concerns. Second objectives, determined the risk rating of facilities hazard at Larkin Jaya Flat by using HIRARC. Last objectives, proceed with the risk control phase by using HIRARC. This research is focused on the Larkin Jaya flat in Johor Bahru. Old high-rise residential facilities that lack a proper risk assessment approach may not be able to operate properly, which might have an impact on the health and safety of their residents. This study used a mixed method, qualitative and quantitative. Qualitative technique which is HIRARC observation checklist at Larkin Jaya flat, supported by quantitative survey methodology at Larkin Jaya Flat. The survey distributed among the residents of Larkin Jaya Flat as the respondent. 30 people were able to take part in this study to support the qualitative data and reach its goals. The collected data been analysed by HIRARC risk matrix table for the observation method and the survey result by frequency in mode. At the end of this study, numerous methods be recommended to reduce the safety and health risk of old high-rise residential facilities by referring to the DOSH guidelines and several studies, since old high-rise buildings require critical preventative maintenance.